Age Related Change in Morphometric Study of Normal Lumbar Intervertebral Disc by MRI in A Tertiary Hospital of Bangladesh (Journal of Chittagong Medical College Teachers' Association, 2022)
Background: Magnetic resonance imaging is the most widely used method of specifically assessing intervertebral disc degeneration. The present study was aimed to evaluate morphology of lumbar intervertebral disc at different vertebral level in relation to age of normal individuals of Bangladeshi population of Chattogram district.Materials and methods: This cross-sectional observational study was conducted in the Department of Anatomy, Chittagong Medical College, Chattogram, during the period April 2021 to March 2022 upon 50 male and 50 female by dividing them into five age groups according to decade. For statistical analysis ANOVA test was done and p-value was considered significant if it was